2004
DOI: 10.3171/ped.2004.100.2.0201
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial pial arteriovenous fistulas with single-vein drainage

Abstract: Intracranial pial arteriovenous fistulas (AVFs) are rare vascular lesions, of which fewer than 90 cases have been reported in the literature. They are composed of one or more arterial feeding vessels and a single draining vein that usually result in a huge varix. Because of the high-flow shunting, a poor prognosis is associated with conservative treatment. Surgical or endovascular treatment also poses various challenges. The authors present the cases of three patients in whom N-butyl-2-cyanoacrylate-assisted e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
53
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 22 publications
2
53
0
Order By: Relevance
“…In particular, NBCA is a useful embolic material in the following situations: (a) cases in which pseudoaneurysms cannot be embolized via selective catheterization using the isolation technique; (b) embolization involving the preservation of the parent artery [56,134,149,163,167,174,183]; (c) cases in which coil embolization might be unsuitable because of the condition of the target vessels, e.g., those involving markedly tortuous, stenotic, or fine vessels [54,72,87,135,138,165]; (d) cases involving patients in a hypocoagulable state (refer to CQ6). Furthermore, vascular embolization with NBCA has also been reported to be useful for nasal bleeding [103,104], hemoptysis [16,141], and gastrointestinal bleeding.…”
Section: International Situationmentioning
confidence: 99%
“…In particular, NBCA is a useful embolic material in the following situations: (a) cases in which pseudoaneurysms cannot be embolized via selective catheterization using the isolation technique; (b) embolization involving the preservation of the parent artery [56,134,149,163,167,174,183]; (c) cases in which coil embolization might be unsuitable because of the condition of the target vessels, e.g., those involving markedly tortuous, stenotic, or fine vessels [54,72,87,135,138,165]; (d) cases involving patients in a hypocoagulable state (refer to CQ6). Furthermore, vascular embolization with NBCA has also been reported to be useful for nasal bleeding [103,104], hemoptysis [16,141], and gastrointestinal bleeding.…”
Section: International Situationmentioning
confidence: 99%
“…The flow and perfusion pressure in pial AVF is high because of the direct arteriovenous shunt, 11) so huge venous varices are not uncommon. 1,3,4,8,20,21) Five of eight patients with conservatively treated pial AVF died. 14) Review of 88 patients with pial AVF found mortality and morbidity rates of 7% and 11%, respectively, following flow disconnection by direct or endovascular surgery.…”
Section: Discussionmentioning
confidence: 99%
“…They form a part of syndromes such as Rendu-Osler-Weber or Klippel-Trenaunay-Weber syndrome, consistent with the fact that a genetic abnormality contributes to their etiology. 5,13,18 Acquired pial AVFs are very rare and are the result of traumatic injury or iatrogenic causes. Our patient had a minor head injury, but it was difficult to identify whether this head injury was the cause of the pial AVF from her initial CT scan.…”
Section: Discussionmentioning
confidence: 99%
“…3,8,18 The goal of treatment is to obliterate the arteriovenous shunt, with preservation of the normal arterial supply and venous drainage of the normal brain tissue. However, the identification of the fistula point is occasionally obscured on digital subtraction angiography.…”
mentioning
confidence: 99%
See 1 more Smart Citation